Hydroxylic protic ionic liquids with two types of basic centers - Shevchenko, V. V.; Gumennaya, M. A.; Stryutsky, A. V.; Trachevsky, V. V.; Klymenko, N. S.; Korolovych, V. F.; Ledin, P. A.; Tsukruk, V. V. (Reports of the National Academy of Sciences of Ukraine, 2016)
1-((3-(1H-imidazol-1-yl)propyl)amino)-3-butoxypropan-2-ol comprising two basic centers of different basicities, which are imidazole and aliphatic amine, is obtained by the reaction of butyl glycidyl ether with 1-(3-aminopropyl)imidazole. The further partial (50 %) or complete neutralization of the obtained compound resulted in protic ionic liquids (IL) containing hydroxyl groups. The identification of synthesized compounds is carried out by using IR and 1H NMR spectroscopy. It is found that the formation of multicenter hydrogen bonds with the rapid proton migration between these centers according to the mechanism of intramolecular and intermolecular transfer in bulk of the IL containing partially neutralized main centers occurs. The obtained compounds are of interest as monomers for the synthesis of macromolecular ionic liquids.